Welfare, inequality and social citizenship : deprivation and affluence in austerity Britain / Daniel Edmiston. - Edmiston, Daniel (Policy Press, 2018)
Offers a rare and vivid insight into the everyday lives, attitudes and behaviours of the rich as well as the poor across the UK, demonstrating how those marginalised and validated by the existing welfare system make sense of the prevailing socio-political settlement and their own position within it.